In silico analysis of myricetin and fisetin as potential B-cell lymphoma extra-large (Bcl-xL) inhibitors in cancer therapy: Myricetin and fisetin as potential Bcl-xL inhibitors - Nordin, Noraziah; Abd Ghani, Mohd Faiz; Roslan, Nuruliza; Riandini Aisyah; Sri Wahyuni; Peni Indrayudha; Em Sutrisna (Journal of Tropical Life Science, 2026)
B-cell lymphoma extra-large (Bcl-xL) is an anti-apoptotic protein that is crucial for cancer cell survival and resistance to chemotherapy. Flavonoids have shown potential as anticancer agents through various pathways, including apoptosis. However, molecular interactions of flavonoids with Bcl-xL remain unknown. This study aims to evaluate the binding affinity and stability of myricetin and fisetin as Bcl-xL inhibitors using in silico approaches, including molecular docking and molecular dynamics (MD) simulations. Molecular docking was performed by AutoDock Vina software to evaluate the binding affinity of myricetin and fisetin to the Bcl-xL protein. MD simulations were conducted using the AMBER 2022.1 package to analyze the stability and dynamic behavior of the flavonoids-Bcl-xL complexes over a 100 ns trajectory. Docking analysis revealed strong binding affinities for both flavonoids, with fisetin exhibiting a slightly higher affinity (-7.6 kcal/mol) compared to myricetin (-7.2 kcal/mol). MD simulations confirmed the stability of both complexes, with myricetin forming a more extensive hydrogen bonding due to its additional hydroxyl groups, contributing to lower RMSD fluctuations and higher structural stability. Binding free energy calculations further supported the favorable interaction of myricetin with Bcl-xL (-61.542 kJ/mol), suggesting its potential as a potent inhibitor. In silico analysis indicates that both myricetin and fisetin have promising inhibitory potential against Bcl-xL, with myricetin demonstrating better stability and binding efficiency. These findings provide a basis for further experimental validation and the potential development of flavonoid-based Bcl-xL inhibitors for targeted cancer therapy.